A study protocol for integrating outpatient services at the primary health care level as part of the universal health coverage benefit package within the national health insurance program of Pakistan through private health facilities - Azmat, Syed Khurram; Thom, Ellen Mpangananji; Arshad, Muhammad; Hamza, Hasan Bin; Aabroo, Atiya; Balal, Asma; Awan, Muhammad Ali; Rifaq, Faisal; Hemachandra, Nilmini; Qudsia, Uzma (Frontiers in Public Health, 2024)
Introduction and aim Pakistan has a mixed-health system where up to 60% of health expenditures are out of pocket. Almost 80% of primary healthcare (PHC) facilities are in the private sector, which is deeply embedded within the country’s health system and may account for the unaffordability of healthcare. Since 2016, the existing national health insurance program or Sehat Sahulat Program (SSP), has provided invaluable coverage and financial protection to the millions of low-income families living in Pakistan by providing inpatient services at secondary and tertiary levels. However, a key gap is the non-inclusion of outpatient services at the PHC in the insurance scheme. This study aims to engage a private provider network of general practitioners in select union councils of Islamabad Capital Authority (ICT) of Pakistan to improve access, uptake, and satisfaction and reduce out-of-pocket expenditure on quality outpatient services at the PHC level, including family planning and reproductive health services. Methods and analysis A 24-month research study is proposed with a 12-month intervention period using a mixed method, two-arm, prospective, quasi-experimental controlled before and after design with a sample of 863 beneficiary families from each study arm, i.e., intervention and control groups (N = 1726) will be selected through randomization at the selected beneficiary family/household level from four peri-urban Union Councils of ICT where no public sector PHC-level facility exists. All ethical considerations will be assured, along with quality assurance strategies. Quantitative pre/post surveys and third-party monitoring are proposed to measure the intervention outcomes. Qualitative inquiry with beneficiaries, general practitioners and policymakers will assess their knowledge and practices. Conclusion and knowledge contribution PHC should be the first point of contact for accessing health services and appears to serve as a programmatic engine for universal health coverage (UHC). The research aims to study a service delivery model which harnesses the private sector to deliver an essential package of health services as outpatient services under SSP, ultimately facilitating UHC. Findings will provide a blueprint referral system to reduce unnecessary hospital admissions and improve timely access to healthcare. A robust PHC system can improve population health, lower healthcare expenditure, strengthen the healthcare system, and ultimately make UHC a reality.